Information avoidance by younger adults with Type 1 diabetes: a preliminary empirical study - Bruce Ryan; Gemma Webster (Information Research: An International Electronic Journal)
Introduction. People with Type 1 diabetes need to collect data to calculate their own insulin doses, and collect information about potential complications. However, information avoidance may be a barrier to such activities.